(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The most pronounced immunological disturbances were observed with lipofilling of the mammary glands, which corresponds to the high clinical complication rate in this area. The data obtained confirm the presence of an immunological predisposition to an unfavorable outcome of the procedure and can serve as a basis for developing a risk prediction system.